2020
DOI: 10.1021/acs.jpca.0c03946
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Dependent Crossover from the Red to Blue Shift of the Donor’s Stretching Fundamental in the Binary Hydrogen-Bonded Complexes of CDCl3 with Ethers and Ketones

Abstract: Mid-infrared spectra for C–D···O hydrogen (H)-bonded binary complexes of CDCl3 with acetone (AC), cyclohexanone (CHN), diethyl ether (DEE), and tetrahydrofuran (THF) have been measured in the vapor phase at room temperature and in an argon matrix at 8 K. Remarkable matrix effect has been observed in each case with respect to the spectral shift of the donor group’s stretching fundamental (ΔνC–D). In the case of complexes with AC and CHN, the sign of ΔνC–D changes from a few wavenumbers positive (blue shift) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…One of the more intriguing developments in the H-bond field was the recent discovery that a number of HBs ignore this rule, and shift their AH stretching frequency to the blue. [21][22][23][24][25][26][27][28][29][30][31] In these cases, the bond length also changes in the opposite direction, contracting instead of elongating. After some initial thought that perhaps this contrary behavior disqualified these interactions as true H-bonds, it was soon agreed that they are indeed H-bonds in all respects, despite their unexpected spectral behavior.…”
Section: Introductionmentioning
confidence: 99%
“…One of the more intriguing developments in the H-bond field was the recent discovery that a number of HBs ignore this rule, and shift their AH stretching frequency to the blue. [21][22][23][24][25][26][27][28][29][30][31] In these cases, the bond length also changes in the opposite direction, contracting instead of elongating. After some initial thought that perhaps this contrary behavior disqualified these interactions as true H-bonds, it was soon agreed that they are indeed H-bonds in all respects, despite their unexpected spectral behavior.…”
Section: Introductionmentioning
confidence: 99%
“…36 A slight C sp 3-H stretching frequency blue-shi of 8.7 cm −1 in C sp 3-H/N nonconventional hydrogen bond was recently observed in the complex between chloroform with acetonitrile in the gas phase using Fourier transform IR (FTIR) spectroscopy by Behera et al 27 Remarkably, a similar change of the C sp 3 -H stretching frequency from blue shi in the gas phase to red shi in the argon matrix was also observed in complexes of deuterated chloroform with acetone and cyclohexanone. 37 Recently, the blue shi of the stretching frequency was found in the C sp 2 -H bond and the extent of stretching frequency was even much higher than that of the C sp 3 -H bond as a proton donor, in spite of the larger polarity of the former with respect to the latter one. Indeed, a C sp 2 -H signicant blue shi by 81 O 96 cm −1 in the C sp 2 -H/O hydrogen bond formed in the complexes of formic acid with formaldehyde and thioformaldehyde has been recently discovered.…”
Section: Introductionmentioning
confidence: 99%
“… 36 A slight C sp 3 –H stretching frequency blue-shift of 8.7 cm −1 in C sp 3 –H⋯N nonconventional hydrogen bond was recently observed in the complex between chloroform with acetonitrile in the gas phase using Fourier transform IR (FTIR) spectroscopy by Behera et al 27 Remarkably, a similar change of the C sp 3 –H stretching frequency from blue shift in the gas phase to red shift in the argon matrix was also observed in complexes of deuterated chloroform with acetone and cyclohexanone. 37 …”
Section: Introductionmentioning
confidence: 99%
“…The other interesting examples are the hindrance of the proton tunnelling in the double-well potential of malonaldehyde [5], and disappearance of the signatures of rotational motion of water, compared to that in the vapour phase [6]. Very recently, Bhattacharya et al [7] have demonstrated that the spectral shifts for the C-D stretching vibration of CDCl 3 in the binary C-D• • • O hydrogen bonded complexes between CDCl 3 and various ethers and ketones are significantly altered, both in terms of sign and magnitude, when confined in an argon matrix compared to the shifts observed in the gas phase. Similar changes in spectral shifts of the C-H stretching fundamental of chloroform of the hydrogen bonded binary CHCl 3 -NH 3 complex were also reported.…”
Section: Introductionmentioning
confidence: 99%